Effects of Biocontrol Product Bio P60 and Liquid Organic Fertilizer on The Development of Fusarium Wilt and Yield of Shallot - Loekas Soesanto; Adi Maulana Yusup; Murti Wisnu Ragil Sastyawan; Endang Mugiastuti; Woro Sri Suharti (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2025)
Shallot production is frequently threatened by Fusarium wilt. Chemical control has proven ineffective, highlighting the need for environmentally friendly alternatives such as the application of liquid organic fertilizer combined Bio P60. The study evaluated the effectiveness of the fertilizer and Bio P60 in controlling the disease and their impact on shallot growth and yield. A completely randomized block design with 16 treatments and three replicates was used, testing Bio P60 application (control, 20 mL per plant applied 1, 3, or 5 times) and the fertilizer (control, 3, 5, or 7 mL L⁻¹). Results showed that the five times application of Bio P60 significantly delayed the incubation period by 61.71%, suppressing disease incidence by 66.67% and reducing AUDPC by 69.84%. Bio 60 also increased plant height by 30.75%, number of leaves by 40.7%, number of bulbs by 75.6%, bulb fresh weight by 104.53%, blub dry weight by 51.1%, and total biomass compared to control. However, the fertilizer application has no significant effect on all variables, and no interaction was found between Bio P60 and the fertilizer. These findings suggest Bio P60 is an effective biocontrol agent for suppressing Fusarium wilt and improving shallot yield, offering a sustainable alternative to chemical treatments.